Strain-induced electronic and optical properties of inorganic lead halide perovskites APbBr3 (A= Rb and Cs). (June 2022) - Islam, Rasidul; Liu, Kong; Wang, Zhijie; Hasan, Soyaeb; Wu, Yulin; Qu, Shengchun; Wang, Zhanguo
Abstract: Recently, inorganic perovskite materials have been achieved with broad consideration in photovoltaic technology owing to their exceptional structural, electronic, and optical properties. This work comprehensively studied the impact of the biaxial compressive and tensile strain on the structural, electronic, and optical properties of the inorganic halide perovskites APbBr3 (A= Rb and Cs) using the first-principles density-functional theory (FP-DFT). This study also initiated to recognize the function of the A-cation on the structural, electronic, and optical properties of the inorganic perovskites. The electronic band structures show that RbPbBr3 and CsPbBr3 are semiconductor materials with a direct bandgap of 1.31 eV and 1.68 eV at the R-point. When considering the spin-orbital coupling (SOC) relativistic effect, the bandgap of the RbPbBr3 and CsPbBr3 perovskites is reduced to 0.282 and 0.478 eV, respectively. Moreover, the bandgap of all the structures shows a reducing trend when the compressive strain is applied and an increasing trend when the tensile strain is introduced. Optical properties like dielectric functions, absorption coefficient, and electron loss function show that these materials have good absorption ability in the visible region due to their band properties. It is found that the peaks of the dielectric constant of APbBr3 (A= Rb and Cs) shift to lower photon energy (redshift) when increasing compressive strain, and in contrast, they show higher photon energy shifting nature (blueshift) when enhancing tensile strain. Therefore, these properties make the APbBr3 (A= Rb and Cs) perovskites very appropriate to apply in light management of solar cells and energy storage devices. Graphical Abstract: ga1 Highlights: The RbPbBr3 and CsPbBr3 compounds are all semiconductors with a direct bandgapof 1.31 eV and 1.68 eV, respectively. The bandgap of RbPbBr3 and CsPbBr3 perovskites is reduced to 0.282 and 0.478 eV, respectively with SOC effect. The bandgap of APbRb3 shows a decreasing trend when the compressive strain is applied. The bandgap of APbBr3 exhibited an increasing trend with increasing tensile strain. The biaxial strain in APbBr3 can significantly increase their absorbance.